Effect of Saline Water for Drip Irrigation on Microbial Diversity and on Fertility of Aeolian Sandy Soils - Xiangxiang Yu; Zhengzhong Jin; Haifeng Wang (Diversity, 2021)
Saline water is widely distributed in the arid environment and sometimes represents the only source of irrigation water to restore and reconstruct vegetation. However, the effects of saline water on the bacterial diversity and fertility level of aeolian sandy soil are not well understood. In this study, we investigated a vegetation belt along the Tarim Desert Highway that has been constructed as a windbreak and consists of desert shrubs and was irrigated with saline water at six levels of salinity along the Tarim Desert Highway. The bacterial diversity was studied using Biolog Eco, a phospholipid fatty acid analysis, and a polymerase chain reaction–denaturing gradient gel electrophoresis, and the soil fertility was calculated and expressed as the integrated fertility index. The soil bacterial diversity (in terms of carbon metabolism, genes, and fatty acid species) was significantly affected by the level of salinity, and the microbial activity was low under high salinity. Fertility was also markedly affected by the degree of salinity and by the depth of soil, being lower at higher salinity levels and in the top layer (0–5 cm), and was also correlated to both the metabolic diversity index of soil microorganisms and the diversity index of fatty acids of soil microorganisms. The genetic diversity index of soil microorganisms shared a polynomial relation with fertility and contributed to it positively and significantly. Therefore, using less saline water for drip irrigation could avoid salt accumulation in soil and arrest its compaction, promote the formation of soil aggregates and the build-up of nutrients, and increase microbial activity, thus playing a crucial role in promoting the circulation, conversion, and utilization of nutrients in aeolian sandy soils and improving the soil quality. The judicious use of saline water, therefore, deserves serious consideration in irrigation practices.